Antitumor and cytotoxic activities of endophytic Enterobacter hormaechei derived secondary metabolites: In-vitro and In-silico study - Muddasir Khan; Sumera Afzal Khan; Chieh-Wei Chang; Chien-Chin Chen; Bokyung Lee; Muhammad Hamayun (PLoS ONE, 2025)
Anticancer therapies resistance, as well as their existing side effects, has become a significant issue worldwide. The demands of new anticancer agents that prevent cancer from developing and growing or spreading are increasing day by day. In this regard, our investigation assessed the cytotoxic and anticancer properties of secondary metabolites (SMs) obtained from understudied endophytic bacteria inhibiting Alliaria petiolata . The identified SMs were further screened by computational analysis against angiogenic factors of cancer. As a result, the leaf sample-associated isolate was identified as Enterobacter hormaechei AP2 strain. Gas chromatography-mass spectroscopy (GC-MS) analysis has shown the existence of 27 compounds present in the crude extract with main compounds being; 4,4-Ethylenedioxy-1-pentylamine (22.54%), Triethanolamine (15.17%) and 2-isobutoxyethyl acetate (12.51%). The extract showed anticancer activity with IC 50 = 145 µM against the human glioblastoma cell line and cytotoxic activity with LC 50 = 214.1 μg/mL against Artemia salina nauplii. The metabolite; 3-(2-Methylpropyl)hexahydropyrrolo[1,2-a]pyrazine-1,4-dione was predictively found most effective by computational analysis against angiogenic factors of cancer. It also demonstrated high intestinal solubility as well as low toxicity. In conclusion, the presence of E. hormaechei within A. petiolata may provide a wealth of bioactive chemicals. Validating the current discovery, purification, its biosynthesis route and other biological functions were recommended for additional research.